A pragmatic stepped-wedge cluster randomized trial to evaluate the effectiveness and cost-effectiveness of active case finding for household contacts within a routine tuberculosis program, San Juan de Lurigancho, Lima, Peru. (November 2020) - Shah, Lena; Rojas Peña, Marlene; Mori, Oscar; Zamudio, Carlos; Kaufman, Jay S.; Otero, Larissa; Gotuzzo, Eduardo; Seas, Carlos; Brewer, Timothy F.
Highlights: Active case finding increases tuberculosis (TB) detection among household contacts. Active case finding is not cost-effective under routine program conditions in Lima. A stepped wedge trial design is useful for evaluating public health interventions. Adding active case finding for TB needs additional resources to be cost-effective. Abstract: Background: Active case finding (ACF) in household contacts of tuberculosis (TB) patients is now recommended for National TB Programs (NTP) in low- and middle-income countries. However, evidence supporting these recommendations remains limited. This study evaluates the effectiveness and cost-effectiveness of ACF for household contacts of TB cases in a large TB endemic district of Lima, Peru. Methods: A pragmatic stepped-wedge cluster randomized controlled trial was conducted in 34 health centers of San Juan de Lurigancho district. Centers were stratified by TB rate and randomly allocated to initiate ACF in groups of eight or nine centers at four-month intervals. In the intervention arm, NTP providers visited households of index patients to screen contacts for active TB. The control arm was routine passive case finding (PCF) of symptomatic TB cases. The primary outcomes were the crude and adjusted active TB case rates among household contacts. Program costs were directly measured, and the cost-effectiveness of the ACF intervention was determined. Findings: 3222 index TB cases and 12, 566 household contacts were included in the study. ACF identified more household contact TB cases than PCF, 199.29/10, 000 contacts/year vs. 132.13 (incidence rate ratio of 1.51 (95% CI 1.21–1.88)). ACF was associated with an incremental cost-effectiveness ratio of US $16, 400 per disability-adjusted life year averted and not cost-effective assuming a willingness-to-pay threshold for Peru of US $6360. Conclusion: ACF of TB case household contacts detected significantly more secondary TB cases than PCF alone, but was not cost-effective in this setting. In threshold analyses, ACF becomes cost-effective if associated with case detection rates 2.5 times higher than existing PCF programs.